Agro-Industrial by-products and farm wastes for poultry production in Nigeria: challenges and opportunities (2011)
The poultry industry in Nigeria requires up Io ninety per cent of the total commercially produced feeds in Nigeria. Conventionally, maize is the major source of energy in poultry feeds in Nigeria, while soybean, groundnut cake and fish meal are sources of protein. Poultry farmers often use alternative feed ingredients whenever the prices of the conventional feed ingredients increase beyond realization of profit. Agro-industrial by-products (AlBs) are mostly cereal and oil seed processing by-products but when poorly stored agro-industrial by-products often go mouldy necessitating the use of toxin binders. The substituability of cassava for maize is almost unity but for the additional processing effort that is required for cassava. Hatchety wastes (eggshell, culled eggs, poorly formed chicks) and slaughter houses (blood, bones, rumen scrapping, and feathers) are of animal origin potentially available for inclusion in feed. The use of animal by-products for componding feeds is however becoming less acceptable. Crop wastes that have potential for use in poultry feeding are cassava leaves and also leaves from other crops. The leaves can be good sources of leaf protein when harnessed. Exogenous enzymes results in cost reduction and improved animal performance. Whereas several of these by-products are available for inclusion in poultry feeds either as energy or protein alternatives, wide Variation in their nutritional compositions and lower quality compared to the conventional feedstuffs create a Situation of challenge in their use. Nevertheless, their potential can be harnessed by guided inclusion levels, further processing, supplementation with exogenous enzymes or a combination of all three factors. In conclusion, to complementing the use of alternatives feed ingredients, the poultry farmer should also be encouraged to increase the efficiency of production by considering proper manipulation of feed, application of appropriate housing System, the use of feed additives among others.